2015
DOI: 10.1039/c5ra07049j
|View full text |Cite
|
Sign up to set email alerts
|

On-line microextraction of moxifloxacin using Fe3O4 nanoparticle-packed in-tube SPME

Abstract: In the current study, an in-tube solid phase microextraction (SPME) approach based on Fe3O4 nanoparticles packed tube for microextraction and detection of moxifloxacin has been reported. In this regard, the Fe3O4 nanoparticles (NPs) were prepared by a batch synthesis and were introduced into a stainless steel tube by a syringe. Afterward, a strong magnet was placed around the tube, so that the Fe3O4 NPs were retained in the tube and the tube was used in the in-tube SPME-HPLC for the analysis of moxifloxacin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…). The Fe3O4 MNPs were synthesized via chemical co-precipitation method according to the previous report [49].…”
Section: Fe 3 O 4 Magnetic Nanoparticles (Fe 3 O 4 Mnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…). The Fe3O4 MNPs were synthesized via chemical co-precipitation method according to the previous report [49].…”
Section: Fe 3 O 4 Magnetic Nanoparticles (Fe 3 O 4 Mnpsmentioning
confidence: 99%
“…Moreover, the incorporation of superparamagnetic iron (III) oxide nanoparticles (Fe3O4 MNPs) to the MOF@GO or MOF@CNT hybrid nanocomposites can be engineered for the magnetic separation and recovery of the absorbents [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…[3]. The other reported methods used a difficult method of preparation and long procedures [2]. A shorter time of contact with GRP-PPY-NP to save time and high efficiency also shows a benefit over the reported methods as they took more time for the process [33].…”
Section: Reusability and Sustainabilitymentioning
confidence: 98%
“…Removal of MXF from wastewater was previously reported using different adsorption methods. However, either a long process of preparation with high costs, time consumption, or high temperature such as non-eco-friendly methods were adopted such as biochars [3], metal-organic framework (MOF) [46], natural zeolite [33], in-tube solid-phase microextraction using stainless steel tube by a syringe loaded with Fe 3 O 4 nanoparticles [2], and removal by long synthesis process of NP [6], which considered complicated processes. The removal of other drugs by using different nanoparticles by adsorption was also performed but they didn't achieve the same results as the current work did.…”
Section: Introductionmentioning
confidence: 99%
“…Two analytical methods have been reported by the research group of Almadi for the determination of fluoroquinolones in human urine [146,147]. Magnetic nanoparticles functionalized with sodium dodecyl sulfate have been employed for in-tube SPME of moxifloxacin [146]. The authors concluded that the SDS molecules acted as a bridging agent between the analyte and the bare Fe 3 O 4 material, and thus an enhancement of its retention was observed.…”
Section: Urinementioning
confidence: 99%